PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS SMART APPS CREATOR UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI SEKOLAH DASAR - Amalia, Choirunisa; Alamsyah, Trian Pamungkas; Pamungkas, Aan Subhan (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This research is motivated by the low ability of students to understand mathematical concepts, and the lack of use of technology in the learning process. This study aims to determine the feasibility of learning media, and to determine the extent to which students' understanding of mathematical concepts has increased after using the developed Smart Apps Creator-based mathematics learning media. The method used in this study is Research and Development (R&D) with the development model being the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This study resulted in learning media based on Smart Apps Creator (android application) on mixed arithmetic operations with whole numbers as the subject of research, students of class VI SDN Margahayu IX Bekasi City. The results of the study found that the learning media developed was "Very Appropriate" to be applied to mathematics learning in class VI SD. This is supported by the validation results from media, material, and learning experts with an average feasibility test result of 89.07%. Meanwhile, the results of the student response questionnaires obtained from small group and large group trials obtained an average acquisition result of 98.08% and included the "Very Positive" category. In addition, there was an increase in the ability to understand students' mathematical concepts after using learning media, which can be proven by the acquisition of an average n-gain value of 0.7 so that the criteria for "Medium" improvement were obtained.